Prevention of Corruption with Early Anti-Corruption Education - Poetri Suradinata; Julianto JJ Kalalo; Marlyn Alputila; Hesty Tambajong (Musamus Journal of Public Administration, 2020)
A clean country, like a healthy body. A clean and healthy Indonesia remains hope. The implementation of anti-corruption education at an early age is the foundation of the morality foundation of future generations who dare to say corruption is forbidden. This research aims to provide new ideas to the public or educators to instill anti-corruption values ​​from an early age. The method used is the literature study of relevant texts in the form of journals and literature. The results of this study are to find an Anti-Corruption Education model that is through the method of democracy, joint search, exemplary methods, live in methods that are suitable for children to have high integrity by instilling anti-corruption values, suitable learning resources to support learning activities PAK is a natural and socio-cultural environment, textbooks and text books, audio visuals, and the internet. Suggestions in this study are to urge the government to require Anti-Corruption Education to be given from elementary schools to tertiary institutions.